JORNALISMO SINDICAL PARANAENSE: características da produção editorial dos jornais de seis sindicatos de Curitiba, PR - Ribeiro, Alexsandro Teixeira (2016)
More than century-old union press plays a fundamental role in the history of class struggles as an instrument of defense of the ideals and causes of workers in Brazil. In order to discuss the journalism practiced in the union press, the present work, master's research fruit in journalism conducted at the Graduate Program in Journalism at the State University of Ponta Grossa (UEPG), is the result of analysis that sought to identify characteristics contemporary journalism union, based on publications six unions representing workers in Parana. This work was developed under theoretical basis for Otto Groth (2011), which recognizes journalism as human cultural production, and under the guidance of comprehensive method of Weberian inspiration, understanding of journalism. Contemporary journalism union, based on the analyzed trade union publications, this research points as a mark of union press the role of their own labor union in the themes addressed and the union board as the predominant speech in the newspapers.